Integrating in situ strategies and molecular genetics for the conservation of the endangered Azorean endemic plant Lotus azoricus - Rúben M. Correia Rego; Luís Silva; Maria Olangua-Corral; Guilherme Roxo; Roberto Resendes; Alejandra G. Herrezuelo; João Bettencourt; Cátia Freitas; Diana Pereira; Mónica Moura (Scientific Reports)
Abstract In this paper, we integrate in situ conservation strategies with population genetic analyses to improve future prospects for preserving the endangered species Lotus azoricus P.W.Ball (Fabaceae), currently found on three islands of the Azores: Santa Maria, Pico, and São Jorge. The two largest populations are in Ponta do Castelo (Santa Maria) and Calheta de Nesquim (Pico). Project LIFE VIDALIA recently implemented a comprehensive conservation plan, which included seed propagation, population reinforcement for four populations on Pico and São Jorge, and control of invasive plant species and rats. To assess genetic diversity and population structure, we analysed L. azoricus populations using retrotransposons. An increase in population size was observed at Calheta de Nesquim following the implementation of these actions, despite the negative impact of Hurricane Lorenzo in 2019. Genetic analysis revealed some admixture, with translocated plants used in reinforcements on Pico showing a distinct founder effect and differing genetic patterns compared to original individuals. Overall genetic differentiation was low, however Saint Lourenço population (Santa Maria) presented significant genetic differentiation. Gene flow between populations was high, likely due to natural or human-mediated seed dispersal. The highest genetic diversity was found at Calheta de Nesquim, likely influenced by gene flow and population growth. Some populations are prioritised for conservation based on high allelic richness and unique genetic markers. To prevent potential loss of genetic diversity, translocation between genetically distinct populations should be avoided. Collaboration between conservation stakeholders and researchers is essential for creating holistic conservation plans, and prior knowledge of population genetics will enable more effective planning.